Synthesis of Molybdenum Disulfide from Waste Mo Materials - Cai, Yong-Kui; Xu, Yong; Wang, Xiao-Qiang; Hu, Kun-Hong (Asian Journal of Chemistry, 2012)
MoS2 was synthesized from waste Mo materials and Na2S by a chemical method. The effect of reaction conditions on the yield of MoS2 and the recovery rate of Mo was investigated. The results showed the yield of MoS2 and the recovery rate of Mo was remarkably influenced by the leaching and extraction conditions, including time, temperature and ratio of liquid to solid. The as-prepared MoS2 comprises clusters of nanoparticles with ca. 100 nm sizes. This work exhibits potential applications in the recovery of waste Mo materials.